SEBARAN JENIS KAYU LAWANG (Cinnamomum cullilawan Blume) DI DESA MOSO KECAMATAN TEHORU KABUPATEN MALUKU TENGAH - Indra, Nandi; Tetelay, Febian; Sahupala, Andjela (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
The objective of this study is to determine the distribution of the Lawang wood species (Cinnamomum cullilawan Blume) in Mosso Village, Tehoru District, Central Maluku Regency. The research used an inventory method by creating plots along transects. Three transects were established in the study area, with a distance of 20 meters between transects, and observation plots measuring 20m x 20m. The results of this study indicate that the species is well-suited to grow in Mosso Village, Tehoru District. Based on the importance value index and the distribution pattern by altitude, Lawang wood (Cinnamomum cullilawan Blume) is the most viable tree species for development in the forests of Mosso Village, Tehoru District, Central Maluku Regency.